2016
DOI: 10.1016/j.dnarep.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of translesion synthesis DNA polymerases in DNA interstrand crosslink repair

Abstract: DNA interstrand crosslinks (ICLs) covalently join the two strands of a DNA duplex and block essential processes such as DNA replication and transcription. Several important anti-tumor drugs such as cisplatin and nitrogen mustards exert their cytotoxicity by forming ICLs. However, multiple complex pathways repair ICLs and these are thought to contribute to the development of resistance towards ICL-inducing agents. While the understanding of many aspects of ICL repair is still rudimentary, studies in recent year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 82 publications
(118 reference statements)
2
69
0
Order By: Relevance
“…Figure 1) (10), and previous biochemical studies showed that translesion synthesis across DNA interstrand cross-link lesions depends highly on their structures. For instance, Ho et al.…”
Section: Discussionsupporting
confidence: 62%
“…Figure 1) (10), and previous biochemical studies showed that translesion synthesis across DNA interstrand cross-link lesions depends highly on their structures. For instance, Ho et al.…”
Section: Discussionsupporting
confidence: 62%
“…Avoidance of double-strand break formation in the glycosylase-dependent unhooking mechanism eliminates the need to engage homologous recombination, a process that is quite complex in its own right and can lead to insertions and deletions in the genome [69, 123]. Both the incision-dependent (Fanconi) and incision-independent cross-link repair pathways include error-prone, potentially mutagenic steps [64, 65, 124], involving the bypass of psoralen adduct remnants [62, 63, 125, 126] and/or Ap sites [127, 128]. …”
Section: Comparison Of Incision-dependent and Incision-independentmentioning
confidence: 99%
“…The replacement of N7-guanine with carbon introduces changes in hydration and charge localization (75). However, 7-deazaguanine-containing DNA has essentially the same structure as native DNA (76), and 7-deazaguanine mimics have been successfully used in a number of previous studies of DNA lesion repair and polymerase bypass (27,(77)(78)(79).…”
mentioning
confidence: 99%